Post authorization safety study comparing quetiapine to risperidone and olanzapine. (13th June 2016) - Heintjes, Edith M.; Overbeek, Jetty A.; Penning‐van Beest, Fernie J. A.; Brobert, Gunnar; Herings, Ron M. C.
Abstract : Objectives: To compare rates of specific adverse outcomes between patients starting quetiapine, olanzapine, or risperidone use in the Netherlands. Methods: Observational study using the PHARMO Database Network, including patients starting quetiapine (4658), olanzapine (5856), or risperidone (7229) in 2000–2009, comparing rates of all‐cause mortality, failed suicide attempts, extrapyrimidal symptoms (EPS), diabetes mellitus (DM), hypothyroidism, and acute myocardial infarction (AMI). Key findings: Median follow‐up until discontinuation/end of follow‐up was 0.6 years. Prescribed doses were generally lower than the approved defined daily doses, especially for quetiapine. Quetiapine was significantly associated with lower EPS rates (HR 0.18; 95% CI 0.13–0.24), but higher failed suicide attempt rates (HR 2.07; 95% CI 1.35–3.16) compared to risperidone. Quetiapine was significantly associated with lower EPS rates (HR 0.59; 95% CI 0.42–0.84) and DM rates (HR 0.66; 95% CI 0.44–0.97) compared to olanzapine. Rates for all‐cause mortality, hypothyroidism, and stroke were similar between groups. AMI events were too infrequent to draw conclusions. Conclusions: Quetiapine was associated with lower EPS, but higher failed suicide attempt rates compared to risperidone. Quetiapine was associated with lower EPS and DM rates compared to olanzapine. The results should be interpreted with caution because of possible channelling and residual confounding. Copyright © 2016 John Wiley & Sons, Ltd.